Farmer adoption of plot- and farm-level natural resource management practices: between rhetoric and reality - Stevenson, James R.; Vanlauwe, Bernard; Macours, Karen; Johnson, Nancy L.; Krishnan, Lakshmi; Place, Frank; Spielman, David J.; Hughes, Karl; Vlek, Paul L.G. (Elsevier, 2019)
There is a significant gap between the rhetoric of claims about adoption of farm-level natural resource management practices and the reality. New empirical evidence of low adoption from several developing countries suggests that on-farm natural resource management practices face significant constraints to adoption, and that they deliver heterogeneous private and public benefits. Five recommendations are given to the research community related to: targeting; scaling-up; the proper role of research; trajectories of diffusion; and measurement of environmental impacts.